Personalized, Electronic Health Record–Integrated Decision Aid for Stroke Prevention in Atrial Fibrillation: A Small Cluster Randomized Trial and Qualitative Analysis of Efficacy and Acceptability. Issue 6 (June 2021) - Schott, Stacey L.; Berkowitz, Julia; Dodge, Shayne E.; Petersen, Curtis L.; Saunders, Catherine H.; Sobti, Navjot Kaur; Xu, Keren; Coylewright, Megan
Abstract : Background: Shared decision-making in cardiology is increasingly recommended to improve patient-centeredness of care. Decision aids can improve patient knowledge and decisional quality but are infrequently used in real-world practice. This mixed-methods study tests the efficacy and acceptability of a decision aid integrated into the electronic health record (Integrated Decision Aid [IDeA]) and delivered by clinicians for patients with atrial fibrillation considering options to reduce stroke risk. We aimed to determine whether the IDeA improves patient knowledge, reduces decisional conflict, and is seen as acceptable by clinicians and patients. Methods: A small cluster randomized trial included 6 cardiovascular clinicians and 66 patients randomized either to the IDeA (HealthDecision) or usual care (clinician discretion) during a clinical encounter when stroke prevention treatment options were discussed. The primary outcome was patient knowledge of personalized stroke risk. Exploratory outcomes included decisional conflict, values concordance, trust, the presence of a shared decision-making process, and patient knowledge related to time spent using the IDeA. Additionally, we conducted semistructured interviews with clinicians and patients who used the IDeA were conducted to assess acceptability and predictions of future use. Results: The IDeA significantly increased patients' knowledge of their stroke risk (odds ratio, 3.88 [95% CI, 1.39–10.78]; P <0.01]). Patients had less uncertainty about their final decision ( P =0.04). There were no significant differences in values concordance, trust in clinician or shared decision-making. Despite training, each clinician used the IDeA differently. Qualitative analysis revealed patients prefer using the IDeA earlier in their diagnosis. Clinicians were satisfied with the IDeA, yet varied in the contexts in which they planned to use it in the future. Conclusions: Using an Integrated Decision Aid, or IDeA, increases patient knowledge and lessens uncertainty for decision-making around stroke prevention in atrial fibrillation. Qualitative data provide insight into potential implementation strategies in real-world practice. Abstract : Supplemental Digital Content is available in the text.